Virtualización de los servidores de la ZRlll-SEDE MOYOBAMBA para el mejoramiento de la calificación registral utilizando WINDOWS SERVER 2008 R2 SP1 HYPER-V - Hernández Castañeda, Jhony Milton (2014)
This thesis makes the study and its importance can have registry virtualization systems optimization Rated Registered in the Receiving Offices Registry Zone N°. III - Moyobamba Headquarters, also in optimizing time of customer service and improving processes access to the systems often become sluggish and hinder the registration worker productivity and I or attorney certifying those found in offices and this leads to the user carry a bad impression of the care provided by workers SUNARP. Using Windows Server 2008-R2 using the Service Hyper-v, a virtual machina with server 2008 standard was created so that there can install the registry systems and these can be used by remate sessions with terminal server from the PC's that are in receiving offices in arder to improve access to systems and accelerate the process of care, registration and issue of advertising. To achieve the proposed objectives, impartial observation and interviews were applied to the users on the registry and received workers receiving offices Uchiza and Nueva Cajamarca, thus achieving data served to validate the hypothesis of this research service. Also could be identified that the advertising service that was providing was inefficient as this process took a long time for the delay in access to the registration system, it was also observad and found that the connection through terminal server this reduced service could improve access times to system registry 5 minutes to about 1 minute in average which shows that the service since improved considerably. Finally with this investigation it was observad and show that with the use of technology can salve these problems and many others for the connection and access to registry systems, thus optimiza the process of land registration and improve the corporate image Public Records regarding the service user.